The taxonomic study of trichome morphology in selected asteraceae species of Pahang, Malaysia - Zainab Sholehah Abdul Rashid,; Che Nurul Aini Che Amri,; Rozilawati Shahari, (Penerbit Universiti Kebangsaan Malaysia, 2022)
A comparative study of foliar trichomes for selected Asteraceae collected in Pahang was observed. The selected species were Ageratum conyzoides L., Tridax procumbens L., Eclipta prostrata (L.) L., Sphagneticola trilobata (L.) Pruski, Emilia sonchifolia (L.) DC. and Youngia japonica (L.) DC. The objective of this study is to document various trichomes among selected Asteraceae species in Pahang. Trichomes are known as one of the micromorphological characteristics that can be investigated for the assisting identification of Asteraceae. The trichomes were examined under a light microscope and Scanning Electron Microscopy (SEM). The trichomes in this study were classified into eight types. The diagnostic characteristics in Ageratum conyzoides consist of glandular trichomes while the non-glandular trichomes are mostly shown in Tridax procumbens. Tridax procumbens showed four diagnostic characteristics which are simple multicellular trichome (coned shape), simple multicellular trichome (long, pointed-end), simple multicellular trichome (long, tapered-end), and stellate trichome. This study proved that data from plant anatomy can be used as supporting data for plant classification in Asteraceae.